Biodiesel production by ethanolysis of palm oil using SrO as a basic heterogeneous catalyst. (2018) - Roschat, Wuttichai; Phewphong, Sunti; Khunchalee, Janeeya; Moonsin, Preecha
Abstract: In this study, SrO was used as a solid catalyst for simple conversion of palm oil to biodiesel production via the ethanolysis reaction. This catalyst has a high basic strength ( H_ ) and a total basic site of about 3725 μmol/g. The results showed that under optimum reaction conditions at catalyst loading amount of 5 wt.%, ethanol/oil molar ratio of 12:1 and reaction temperature 80 °C; 98.2% yield of fatty acid ethyl ester (FAEE or biodiesel) could be achieved in 3 h. The SrO catalyst can be reused for at least 5 times with excellent catalytic activity without regeneration or treatment. The obtained biodiesel product after purification and treatment process shows high quality fuel properties according to ASTM D6751 and EN 14214 standards for bio-auto fuels. The results indicated that transesterification of palm oil with ethanol using SrO as a basic heterogeneous catalyst is a commercially viable way for biodiesel production in the industrial scale.